2018
DOI: 10.1101/307967
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Genome of BAM-degrading Aminobacter sp. MSH1 with Several Low Copy Plasmids

Abstract: 6As one of the only described degraders of the recalcitrant metabolite 2,6-dichlorobenzamide (BAM) of the 7 pesticide dichlobenil, Aminobacter sp. MSH1 has been intensively studied for its characteristics with regards 8 to physiology and its use in bioremediation. Two plasmid sequences from strain MSH1 have previously been 9 published, while the remaining genome sequence has been left uninvestigated. We here present the 10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…MSH1 originally isolated and described by Sørensen et al (2007) was applied in the present study. MSH1 showed great potential for BAM degradation of membrane retentate water in batch studies (Hylling et al, 2019) and it was recently characterized by full genome sequencing (Nielsen et al, 2018). The strain was pre-grown in MSNC medium for 5 days at 20 • C on an orbital shaker (100 rpm).…”
Section: Bacterial Strain and Cultivationmentioning
confidence: 99%
See 1 more Smart Citation
“…MSH1 originally isolated and described by Sørensen et al (2007) was applied in the present study. MSH1 showed great potential for BAM degradation of membrane retentate water in batch studies (Hylling et al, 2019) and it was recently characterized by full genome sequencing (Nielsen et al, 2018). The strain was pre-grown in MSNC medium for 5 days at 20 • C on an orbital shaker (100 rpm).…”
Section: Bacterial Strain and Cultivationmentioning
confidence: 99%
“…A novel primer set was designed to verify that bbdA gene presence corresponded to presence of MSH1 cells. This primer set specifically targets a prophage-insertion-region on the genome of MSH1 (Nielsen et al, 2018), following an analogous method used by Gobbi et al (2020). The prophage sequences in the MSH1-genome were identified by using PHASTER (PHAge Search Tool Enhanced Research) from Arndt et al (2016).…”
Section: Quantification Of Bbda Genes Msh1 Cells and Total 16s Genesmentioning
confidence: 99%
“…Previous studies on Aminobacter sp. MSH1 reported that 2,6-dichlorobenzamide (BAM) degradation genes map on distinct plasmids: pBAM1 carries the BbdA amidase, responsible for the initial transformation of BAM into 2,6-DCBA [ 65 ], whereas pBAM2 harbors a large region for the complete degradation of 2,6-DCBA, encompassing two major gene clusters: bbdR1B1B2B3CDE and bbdR2FGHIJ [ 30 , 66 ] ( Supplementary Table S5 ). Genome inspection of all Aminobacter members detected BAM degradation genes only in Aminobacter sp.…”
Section: Resultsmentioning
confidence: 99%
“…The Aminobacter genus of the Phyllobacteriaceae family is present in the microbial consortia MG Kraft 37°C and BY Kraft 37°C in the sixth passage (Figs 2 , 3 and 4 ). Although no previous studies of enriched microbial consortia for lignin degradation have identified species of the genus Aminobacter , sequencing of the genome from a member of this genus indicates the presence of a ligninolytic enzyme, a laccase [ 63 ]. This representative of the genus in our experiments may have a role on the degradation of lignin, indicating the need for further characterization of the activities by bacteria of this genus.…”
Section: Discussionmentioning
confidence: 99%